(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Available data showed that the intestine increases it glucose uptake in response to hyperglycemia induced by any cause. However, what the intestine does with the glucose is not known. This study investigated the metabolic fate of the glucose taken up by the intestine during hyperglycaemia in dogs. Experiments were carried out on fasted, male, anaesthetized mongrel dogs divided into 4 groups. The control (group 1, n=5) received normal saline (0.2 ml/kg) while groups 2-4 (subdivided into two as low or high dose, n=5 each) received adrenaline (1 μg/kg or 5 μg/kg), glucagon (3 ng/kg or 8 ng/kg) and glucose (10 mg/kg/min or 20 mg/kg/min). Through a midline laparatomy, the upper jejunum was cannulated for Intestinal Blood Flow (IBF) measurement. Blood glucose and lactate levels were determined using glucose oxidase and lactate dehydrogenase methods, respectively. Intestinal Glucose/Lactate Uptake (IGU/ILU) was calculated as the product of IBF and arterio-venous glucose /lactate difference [(A-V) glucose/lactate]. Jejunal tissue samples were obtained for the determination of Glycogen Content (GC) and activities of Glycogen Synthase (GS), Glycogen Phosphorylase ‘a’ (GPa), hexokinase and glucose-6-phosphatase. Anthrone method was used to determine GC while activities of GS, GPa, hexokinase and glucose-6-phosphatase were determined spectrophotometrically. Data were subjected to descriptive statistics and analyzed using student’s t-test and ANOVA at α0.05. Arterial and venous blood glucose and lactate were increased by adrenaline, glucagon and glucose. Venous lactate was higher than arterial lactate in all groups. Intestinal blood flow, (A-V) glucose and (A-V) lactate were increased in all the experimental groups. Intestinal glucose uptake increased by 624% (adrenaline), 705% (glucagon) and 589% (glucose) while intestinal lactate release increased by 422%, 459% and 272% respectively. Intestinal GC increased from 138.72 ± 4.58 mg/100 g to 167.17 ± 4.20 mg/100 g (adrenaline), 229.21 ± 6.25 mg/100 g (glucagon) and 165.17 ± 4.20 mg/100 g (glucose). Adrenaline and glucose had no effect on GS activity but it was increased by glucagon; GPa was decreased while hexokinase activity was increased by adrenaline, glucagon, and glucose. Glucose-6-phosphatase activity was not affected by adrenaline and glucagon but decreased by glucose. The intestine modulates blood glucose levels through lactate formation, glycogen formation and most probably conversion of lactate to glucose through gluconeogenesis